Wall Passing as a Training Method for Basic Sepak Takraw Skills: Passing Dengan Tembok Sebagai Metode Latihan Sepak Takraw Dasar - Amanda Virginia; Deka Ismi Mori Saputra; Raja Bani Pilitan; Ikhsan Maulana Putra; Desi Tri Susanti (Academia Open, 2025)
General Background: Sepak takraw requires strong fundamental skills, particularly sepak sila passing, to ensure effective gameplay. Specific Background: However, the mastery of passing techniques among PSTI Merangin athletes remains low due to monotonous and traditional training methods. Knowledge Gap: There has been no scientific evidence examining the effectiveness of wall passing drills in developing sepak sila passing skills. Aims: This study aimed to evaluate the application of wall passing training on the sepak sila passing ability of PSTI Merangin athletes. Results: An experimental design with one group pretest-posttest was conducted on 15 athletes, showing an average score improvement from 6.00 to 7.40. A paired t-test yielded a value of 6.548 with a significance of 0.000 (p<0.05), indicating a significant increase in passing skills. Novelty: Wall-based training proved to be a simple yet effective self-training method for building muscle memory, accuracy, and movement consistency in sepak takraw passing. Implications: These findings provide practical contributions for coaches and physical education teachers as an affordable, independent, and applicable training alternative in sepak takraw development. Highlight: Wall passing training improves accuracy and control in sepak sila passing. A simple method suitable for regional-level athletes. Relevant for practical training programs in schools and clubs. Keywords: Sepak Takraw, Passing, Fundamental Skills, Wall Training, Athlete Performance